An actigraphy study of sleep and pain in midlife women. Issue 7 (July 2015) - Kravitz, Howard M.; Zheng, Huiyong; Bromberger, Joyce T.; Buysse, Daniel J.; Owens, Jane; Hall, Martica H.
Abstract Objective We examined whether women reporting nighttime pain would have more actigraphy-measured evidence for disturbed sleep and would report feeling less rested compared with women without nighttime pain. Methods Up to 27 consecutive nights of actigraphy and sleep diary data from each participant were analyzed in this community-based study of 314 African-American (n = 118), white (n = 141), and Chinese (n = 55) women, aged 48 to 58 years, who were premenopausal, perimenopausal, or postmenopausal and were participating in the Study of Women's Health Across the Nation Sleep Study. Dependent variables were actigraphy-measured movement and fragmentation index, total sleep time, sleep efficiency, and diary self-report of "feeling rested" after waking up. All outcomes were fitted using linear mixed-effects models to examine covariate-adjusted associations between the independent variable (nighttime pain severity) and sleep outcomes. Results Higher pain severity scores were associated with longer sleep duration but reduced sleep efficiency and less restful sleep. Women reporting nocturnal vasomotor symptoms had more sleep-related movement and sleep fragmentation, had reduced sleep efficiency, and were less likely to feel rested after wakening whether or not they reported pain. Conclusions Midlife women who report higher nighttime pain levels have more objective evidence for less efficient sleep, consistent with self-reported less restful sleep. Nocturnal vasomotor symptoms also can contribute to restlessness and wakefulness in midlife women.